Regulator supervisory power and bank loan contracting - He, Zhongda; Qiao, Guannan; Zhang, Le; Zhang, Wenrui (Journal of Banking & Finance, 2021)
Using a sample from 38 economies, we examine the relation between bank regulators’ supervisory power and loan spreads. We find that loans issued by banks in economies with more powerful supervisors have higher spreads. The positive association is more pronounced when firms have lower credit quality, when the relationships between firms and banks are less established, when syndicate loans involve fewer lenders, and when lead banks have a riskier profile. Further analyses reveal that loans issued by banks that operate under more powerful supervisors have smaller size and shorter maturity, and the loans are more likely to have collateral requirements and restrictive covenants. Overall, these results suggest that stronger supervisory power of bank regulators affects loan contracting by mitigating lenders’ excessive risk taking.